EVALUASI RUANG KELAS GAMBAR MANUAL UNTUK MENINGKATKAN KENYAMANAN PADA MASA PANDEMI DI SMK NEGERI 6 BANDUNG - Sumanta, Vena Ventiany; Permana, Asep Yudi; Mardiana, Riskha (Jurnal Arsitektur ZONASI, 2023)
A disease similar to pneumonia emerged in late December 2019 in Wuhan, China. An illness caused by a virus that spreads rapidly until 66% of workers at the fish market get infected. WHO declared that the plague caused by the SARS-CoV-2 virus was a global pandemic on March 11, 2020. The government decided to restrict the activities held in public places, including closing schools and holding distance learning during the pandemic. Reopening schools has to be aware of a few things because this virus can spread directly or indirectly (the objects that are contaminated or airborne). To minimize the virus spread, the thermal condition and lightning in the classroom have to be according to the standards. This research uses evaluative research with a qualitative approach. The evaluative research is used to investigate the compatibility of the drawing studio with the regulation of facilities and infrastructures is Permendikbud No. 34 Tahun 2018 and guidelines to school reopening during Covid-19 pandemic according to PAUDDIKDASMEN also for thermal, lightning comfort are according to ASHRAE and SNI. The outcomes of this research are both the infrastructures also the facilities haven't reached the standard yet. However, some of the facilities are already compatible with the regulation.  The reopening plan for the drawing studio needs some changes, including limiting the students in the classroom, reorganizing the drawing desk within 1,5 m distance, confirming there are cleaning schedules for the studio by disinfecting the whole classroom, and also wiping the surface touched by the pupils. Thermal and lighting conditions are still haven't reached the standard yet. However, the humidity in the drawing studio is already compatible with the regulation.Keywords: Drawing studio evaluation; Covid-19 Pandemic; Thermal and Visual Comfort.